Gender norms, agency, power relations research developed by MAIZE and WHEAT guides other CGIAR and partner researchers impact pathway and scaling interventions - CGIAR Research Program on Maize (2020)
Since 2018, researchers and colleagues from within and outside of CGIAR centers have applied gender-responsive research methods in an attempt to unravel the complex social landscapes of different agricultural settings around the world. They assessed the dynamics of gender norms, power relations, labor-use, and processes for decision-making in access to and control of resources. These assessments guide own and other CGIAR and partner research on how social dynamics influence decisions in adoption of climate-smart, energy-saving and cost-effective agricultural technologies.